2022
DOI: 10.1186/s12951-022-01692-3
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterials: small particles show huge possibilities for cancer immunotherapy

Abstract: With the economy's globalization and the population's aging, cancer has become the leading cause of death in most countries. While imposing a considerable burden on society, the high morbidity and mortality rates have continuously prompted researchers to develop new oncology treatment options. Anti-tumor regimens have evolved from early single surgical treatment to combined (or not) chemoradiotherapy and then to the current stage of tumor immunotherapy. Tumor immunotherapy has undoubtedly pulled some patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 284 publications
(242 reference statements)
0
15
0
Order By: Relevance
“…It is well established that the immune system plays a critical role in cancer development and progression. [6][7][8][9][10] In recent years, there has been growing interest in the relationship between neutrophils and cancer. Neutrophils, the most abundant type of white blood cells in the body, are traditionally thought to play a role in acute inflammation and host defense against infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that the immune system plays a critical role in cancer development and progression. [6][7][8][9][10] In recent years, there has been growing interest in the relationship between neutrophils and cancer. Neutrophils, the most abundant type of white blood cells in the body, are traditionally thought to play a role in acute inflammation and host defense against infection.…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that the immune system plays a critical role in cancer development and progression 6–10 . In recent years, there has been growing interest in the relationship between neutrophils and cancer.…”
Section: Introductionmentioning
confidence: 99%
“…It can block cell division at the G2/M phase Shi (2020) Frontiers in Bioengineering and Biotechnology frontiersin.org shell made of large pores of mesoporous silica (UCMS) simultaneously loaded with photosensitizer molecules, the AL-9 peptide vaccine from the IDO, and the inhibitors of PD-L1, and tested it in Lewis murine lung carcinoma cell line and mouse model. The components of the designed UCMS@Pep-aPDL1 were shown to be capable of potentiated local and systemic anti-tumor immunity through stimulating the killing of IDO-expressed tumor cells, inducing immunogenic cell death, and promoting the infiltration of effector T-cell (Wang et al, 2021;Chen et al, 2022). The STK11 gene (LKB1), encoding serine/threonine kinase 11, is deleted or inactivated in nearly half of NSCLC patients with activated KRAS mutations.…”
Section: Nanoparticles In Lung Cancer Immunotherapymentioning
confidence: 99%
“…Cancer immunotherapy has already received FDA approval and can be effective even for late-stage diagnosis. Clinical research has shown that when cancer immunotherapies are effectively formulated into nanoparticles, they generate much stronger and longer-lasting anticancer activity than administered as free drugs, which is an adaptive and enduring treatment method (Chen et al, 2022). Nanoparticles have shown vast improvements in the delivery of immunostimulatory agents through physicochemical manipulation for cancer immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8–10 ] Therefore, immunotherapy‐based anti‐tumor strategies are a top priority and have resulted in the approval of several immunotherapeutic agents by the Food and Drug Administration (FDA) for over 50 cancer types. [ 11 ] However, like existing treatment options, immunotherapy is not beneficial for every individual. The TIME poses challenges such as heterogeneity of antigen expression, low bioavailability, and excessive tumor immunosuppressive microenvironment, resulting in low response rates and adverse toxic effects.…”
Section: Introductionmentioning
confidence: 99%